2016
DOI: 10.1039/c6nr03869g
|View full text |Cite
|
Sign up to set email alerts
|

Smart surface-enhanced Raman scattering traceable drug delivery systems

Abstract: Smart surface-enhanced Raman scattering traceable drug delivery systems Nanoscale, 2016; 8(25) can be amplified by SERS. Importantly, non-destructive SERS will provide the designed DDS with great autonomy and potential to study the dynamic procedures of non-fluorescent drug delivery into living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Based on the intensity of the marker bands and the position of SERS shifts, the conclusion can be made that only [Au(C,N,N)(OH)][PF 6 ] was detected with a significant presence in both membrane and nuclear cell fractions. It seems that [Au(C,N,N)(OH)][PF 6 ] was found unaltered in these fractions, as also found previously for some drugs [22,25,65,66]. However, low-intensity SERS signals with some of the characteristic shifts can also be recognized for the other two complexes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Based on the intensity of the marker bands and the position of SERS shifts, the conclusion can be made that only [Au(C,N,N)(OH)][PF 6 ] was detected with a significant presence in both membrane and nuclear cell fractions. It seems that [Au(C,N,N)(OH)][PF 6 ] was found unaltered in these fractions, as also found previously for some drugs [22,25,65,66]. However, low-intensity SERS signals with some of the characteristic shifts can also be recognized for the other two complexes.…”
Section: Discussionsupporting
confidence: 80%
“…The identification and localization of drugs inside cells are of vital importance for their medical application as well as for the investigation of their fate and their influence on inner cell organs and components [21,22]. In general, the nanoparticles (NPs) surface and core properties can be manipulated for specific applications such as molecular recognition, chemical sensing, and imaging [23][24][25]. For this purpose, drug-functionalized noble metals NPs (AuNPs, AgNPs) in combination with nanotechnology-based methods (atomic force microscopy (AFM), surface-enhanced Raman spectroscopy (SERS), and fluorescence spectroscopy), may represent an excellent nanoplatform for developing drug delivery and biosensing systems [24,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the biocompatibility and unique optical, physical, and electronic properties of gold nanoparticles (AuNPs) they are extensively used for targeted drug delivery in biomedical nanotechnologies [14,15]. It has also been reported that the intracellular drug delivery site can be monitored using surface enhanced Raman scattering (SERS) due to the surface plasmon resonance properties of the AuNPs [16,17]. AuNPs are often modified with polymers such as poly(ethylene glycol) (PEG) to improve its stability without altering its associated biocompatibility but simultaneously improving its potential in applications in the biomedical field [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…h-SiO 2 NPs were synthesized through a soft-templating method with slight modification using TEOS as silica precursor, TEA as base catalyst, CTAT as structure-directing agent [20,24]. Typically, 0.48 g CTAT and 0.087 g TEA were dissolved in 25 mL DI water (80°C).…”
Section: Preparation Of Ag 3 Po 4 @H-sio 2 Nanoparticlesmentioning
confidence: 99%
“…Inspired by our research on exploring hierarchical porous silica for biopharmaceutical applications [23][24][25], we here develop a facile in situ precipitation approach to load 10 nm Ag 3 PO 4 NPs onto the thiol modified hierarchical porous silica to generate the Ag 3 PO 4 @h-SiO 2 and investigate their photocatalytic disinfection performance. Such a unique structure possesses obvious advantages of high specific surface areas, high Ag 3 PO 4 loading, reduced Ag 3 PO 4 aggregation, better chemical and physical durability.…”
Section: Introductionmentioning
confidence: 99%